Trends in incidence and mortality of acute myocardial infarction in Xiaoshan District， Hangzhou City from 2017 to 2023 - GAO Yuanyuan; WANG Fenjuan; WANG Dongfei; LI Yurong; JIANG Yuanyuan; ZHAO Fangfang; XIAO Duanduan; LIN Junying (Shanghai yufang yixue)
ObjectiveTo analyze the incidence rate and mortality of acute myocardial infarction (AMI) and their changing trends among the registered residents in Xiaoshan District, Hangzhou City from 2017 to 2023, so as to provide references for formulating policies related to AMI prevention.MethodsThe morbidity and mortality data of AMI among the registered residents in Xiaoshan District from 2017 to 2023 were collected through the Hangzhou Chronic Disease and Death Cause Monitoring System. Software such as Excel 2019, SPSS 25.0 and Joinpoint 4.9.1.0 were used to calculate the incidence rate, mortality, and average annual percentage change (AAPC) of AMI.ResultsFrom 2017 to 2023, the average annual crude incidence rate, age-standardized incidence rate using China standard population (ASIRC), and the age-standardized incidence rate using World standard population (ASIRW) of AMI in Xiaoshan District were 48.25/100 000, 29.14/100 000, and 21.64/100 000, respectively, and, from which the AAPCs were 5.495%, 6.010%, and 6.533%, respectively, all showing an upward trend. The average annual crude mortality rate, the age-standardized mortality rate using China standard population (ASMRC), and the age-standardized mortality rate using World standard population (ASMRW) were 11.76/100 000, 6.52/100 000, and 4.71/100 000, respectively, from which the AAPCs were -9.669%, -10.433% and -9.615%, respectively, all showing a downward trend. The average annual crude incidence rate of AMI was higher in males (65.87/100 000) than that in females (31.31/100 000). Moreover, the average annual crude mortality rate of AMI was higher in males (14.08/100 000) than that in females (9.52/100 000), and the difference was statistically significant (all P<0.001) .After age grouping, the crude incidence rate of AMI among the residents aged 35-, 45-, 55-, and 65- years in Xiaoshan District from 2017 to 2023 showed an upward trend over time, with AAPCs of 16.993%, 17.149%, 8.523%, and 5.002%, respectively. While the crude mortality rate in residents aged 35-, 75-, and 85-102 years showed an decreasing trend over time, with AAPCs of -23.977%, -15.467%, and -17.415%, respectively, but there was no statistically significant difference in the trends in incidence rate and mortality of other age groups (all P>0.05).ConclusionThe situation of AMI prevention and control among the registered residents in Xiaoshan District is not optimistic, and targeted measures should be strengthened for the male residents aged ≥35 years old.